Women Linguistic Features in the Craig Gillespie’s Movie “I, Tonya” - Kadek Purnata; Made Budiarsa; Ni Ketut Sri Rahayuni (Udayana Journal of Social Sciences and Humanities, 2021)
Lakoff's assertion about women's language was a breakthrough in linguistics. However, many linguists and researchers also criticized and stated different perspectives towards Lakoff's theory. Therefore, this study was conducted in order to know whether Lakoff's theory is still relevant nowadays. This study used the movie “I’ Tonya” as the data source. It was applied with quantitative and qualitative analysis. It is a documentation method supported with a corpus analysis based on the concordance technique using AntConc software. The findings show that nine types of women's linguistics features were used by the female characters in the “I’ Tonya” movie. Meanwhile, one type of women linguistics feature of the precise color term was not found. From 10677 words of corpus data from “I’ Tonya” subtitles script, women used lexical hedges accounting for 64% while men only 36%. It was also found in intensifier where women used accounting for 103 expressions and men only 37 expressions. However, in avoidance of strong swear words, women were using swear words about 71% compared to only 28% used by men.